Palestine: un féminisme de libération - Elia, Nada; Hammar, Liza; Dupuis-Déri, Francis (Micro r-m, 2024)
"Comment expliquer qu’Israël, malgré ses attaques meurtrières à Gaza et sa violation du droit international, reste à l’abri de toute véritable critique? Pourquoi de nombreuses féministes du Nord global, si promptes à dénoncer l’impact du «fondamentalisme islamique» sur les femmes palestiniennes, restent-elles silencieuses quand il s’agit de décrier l’occupation et le génocide que perpétue l’État israélien en Palestine? En déconstruisant les associations fallacieuses entre antisionisme et antisémitisme, la professeure et militante palestinienne Nada Elia, qui vit aujourd’hui aux États-Unis, rappelle la place des femmes et des personnes queers dans la lutte pour la libération de la Palestine, et revendique le démantèlement des structures coloniales qui écrasent la population à Gaza et en Cisjordanie."-- Site de l'éditeur.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; antisionisme; antisémitisme; approches et analyses; asie; cours; discipline; disicpline; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; militance; palestine; pol4212; premier cycle; privilèges; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Ogimah Ikwe: Native Women and Their Path to Leadership - Lajimodiere, Denise K. (Wicazo Sa Review, 2011)
Much documentation gathered on Native American women's activities originated in the journals of European male missionaries and explorers. These first visitors observed Native societies through the eyes of their own culture, a culture in which male activities were the only happenings of note. 1 This bias led to indirect and distorted descriptions of Native American women's activities and beliefs. 2 Scholars who study Native American women today have made significant inroads into their histories; however, many interpretations remain incorrect and undeveloped. Devon Mihesuah states, "Because many authors write from a patriarchal or white feminist perspective, the value of Indian women is vastly underrated." 3 Gretchen Bataille and Kathleen Sands address this shortcoming, saying, "The portrayal of American Indian women in North America over the last four centuries offers an uneven body of documentary evidence about the lives of Native women as individuals and members of their group." This study's purpose is to increase the visibility of Native American women in leadership roles by recording the voices and histories of nine Native American women leaders. It focuses on the experiences, perceptions, and beliefs of the women interviewed, giving a voice to nine of today's Native American female leaders, nine Ogimah Ikwe (leader women).
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cours; discipline; discours dominant; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; histoire et politique; patriarcat; pol4105; premier cycle; premières nations; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; travail; états-unis

Le genre d’une migration post-coloniale : de Meknès (Maroc) à Montréal (Québec) - Yolande Cohen (Genre & Histoire, 2010)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afrique; afrique du nord; amériques; approches et analyses; canada; cours; discipline; ethnographie; france; his4830; histoire; histoire du féminisme; histoire et politique; immigration; justice sociale; maghreb; maroc; migration; militance; mouvements des femmes*; mouvements féministes; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Firekeepers of the twenty-first century: First Nations women chiefs - Voyageur, Cora Jane (McGill-Queen's Native and northern series, 2008)
A quiet revolution is occurring in Canada's First Nations communities, with changes taking place on social, political, and economic fronts and a significant redistribution of power. Changes to the Indian Act in 1951 paved the way for women to become officially involved in reserve politics, and with governments responding to the demand of First Nations for self-government, positions once held exclusively by men are now being filled by women. Beginning with Elsie Knott, the first female chief in Canada, Cora Voyageur presents the lives of sixty-four of the ninety women chiefs who have assumed the traditionally male role of elected First Nations leadership. Using a range of qualitative research strategies, surveys, participant observation, interviews, and discussions with focus groups, Voyageur presents the colonial histories behind the issues that contemporary Aboriginal communities struggle with and delineates the resulting leadership dilemmas for chiefs, while also articulating a story that is unique to First Nations women. Voyageur asks women chiefs about what inspired them to become leaders, how they've maintained their priorities, and the personal and professional costs and rewards involved in their positions. Firekeepers of the Twenty-First Century is a groundbreaking work that examines the experiences of women as they negotiate multiple roles and navigate the worlds of gender, race, and reserve politics.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; entretien; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; féminisme décolonial; gouvernance; histoire et politique; militance; pol4105; pouvoir; premier cycle; premières nations; périodes historiques; régions géographiques; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques

La scission politique du féminisme international sur la question du “ trafic des femmes ” vers la “ migration ” d’un certain féminisme radical ? - Toupin, Louise (Recherches féministes, 2003)
Cet article donne un aperçu de l’argumentation qui met en lumière et différencie les principales coalitions internationales féministes luttant contre ce qui est couramment appelé le « trafic des femmes ». L’argumentation mise en évidence ne touche que la définition du phénomène et le différend qui sépare les coalitions sur le sujet, ainsi que leurs stratégies respectives pour l’éradiquer. L’auteure souligne en conclusion certains tangentes du féminisme radical qui, à son avis, se voient désormais remises en cause à l’occasion du débat sur les migrations des femmes. Ce débat entraînera-t-il, à son tour, se demande-t-elle, la migration d’un certain féminisme radical ?
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; histoire du féminisme; histoire et politique; intersectionnalité; miitance; patriarcat; premier cycle; prostitution; périodes historiques; ressource en ligne; science politique; science politique et droit; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; traite des femmes; travail; travail du sexe; violences

Thunder in my soul: a Mohawk woman speaks - Monture-Angus, Patricia (Fernwood Publishing, 1995)
"This book contains the reflections of one Mohawk woman and her struggles to find a good place to be in Canadian society. The essays, written in enjoyable and accessible language, document the struggles against oppression that Aboriginal people face, as well as the success and change that have come to Aboriginal communities. It speaks to both the mind and the heart."--Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; mohawk; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques